The role of tax policy in the development of the Iraqi economy: (Applied Research for the period from 1995 to 2010) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The tax policy is an important tool of fiscal policy tools which is usedasits multiple tools the State seeks to achieve objectives, such as theachievement of economic development.The importance of the research comes from the importance ofeconomic development resulting from economic policies and prudent fiscaland appropriate to the economic situation of Iraq at the moment is the mostimportant tax policy that taxes one of the most important financial instruments.The research aims to clarify the role of tax policy in developing of theIraqi economy.In an effort to achieve the goals researchers tried to prove thehypothesis ((The tax policy and through multiple tools that seeks to contributeto the achievement of economic development in Iraq)).The research found several of most important conclusions (doublerole of tax policy in achieving economic development in the duration ofresearch, the percentage of tax revenues to GDP (1.18%)).One of the most important recommendations were (focus on aspectsthat will achieve economic development planning and policy-making tax inorder to activate the role of fiscal policy in economic development).